Tree-based Control Space Structures for Discrete Metric Sources in 3D Meshing - Głut, Barbara; Jurczyk, Tomasz (Computer Science, 2019)
This article compares the different variations of the octree and kd-tree structures used to create a control space based on a set of discrete metric point-sources. The control space thus created supervises the generation of the mesh providing efficient access to the required information on the desired shape and size of the mesh elements at each point of the discretized domain. Structures are compared in terms of computational and memory complexity as well as regarding the accuracy of the approximation of the set of discrete metric sources in the created control space structure.